Effectivity of Intravenous Lidocaine in Pain of Neuropathic Origin - Naveed Ahmed Durrani, Adnan Umer, Sumara Tabassam, Abdul Wasay Toor, Faiza Irshad, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In order to accomplish the goals of this research project, lidocaine was administered intravenously (IV) to patients who were experiencing neuropathic pain. The researchers had an interest in gaining a deeper understanding of the connections that exist between effect and concentration, as well as graded and quanta1 dose-response. Study Place: Kulsoom International Hospital Islamabad Study Duration: 6months (Feb 2021 To July 2021) Methods and Materials: Fifteen patients received an intravenous dose of lidocaine at a rate of 8.35 milligrams per minute for a total of one hour. During the course of the study, both venous blood samples and visual analog pain scores were collected at regular intervals of ten minutes for duration of sixty minutes. In addition, blood samples were taken in order to determine the concentrations of lidocaine in the serum as well as the amount of water in the serum both at the start of the analgesia as well as when the patient had reached their maximum level of pain relief. In order to determine the levels of lidocaine, a technique known as gas chromatography was performed. Result: In addition to graded dose-response curves for each participant and the group, a quanta1 dose-response curve was created. Besides graded dose-response curves, this was done. Also done: graded dose-response curves. The dose-response relationship for IV lidocaine showed large pain relief for modest dose changes. Despite moderate dosage increases, this was true. This was when the drug was given. The ED administered 370.0 mg of lidocaine, but the ED administered 415.5 mg (5 min of infusion). Similar to the link between concentration and effect, 0.60 pg/mL of lidocaine significantly reduced pain. It’s intriguing that serum lidocaine concentration didn’t correlate better with analgesia onset or end than free lidocaine concentration did. Free lidocaine concentration correlated with analgesic effect. Lidocaine concentration in the serum was a stronger predictor of analgesia. Conclusion: This suggests that IV lidocaine’s analgesic mechanism may not follow a concentration-effect connection. The evidence shows this. Intravenous lidocaine is significantly stronger than oral. The analgesic response to intravenous lidocaine is a quick "break in pain" over a narrow dosage and concentration range. This was true independent of lidocaine dose. It doesn’t matter how much lidocaine is given.